Metaphisical monism and taxonomic pluralism (Culturas Científicas, 2018)
I argue against the Marc Ereshefsky’s interpretation according to which Willi Hennig is committed to metaphysical pluralism in his theory of phylogenetic systematics although from the taxonomic point of view he is a monist. I claim that the correct thesis is just the opposite. Hennig is a metaphysical monist but a taxonomic pluralist, since he argued that there is only one correct system of causal relations between the states of an individual organism, the genealogical relations between those individuals, and the phylogenetic relationships among species that are also conceived as individuals from an ontological viewpoint. According to Hennig, even though a plurality of classifications are possible on the basis of relations of similarity among characters, the categories related to these classifications are abstractions and they lack of individuality and reality.
Keywords: Henning; metaphysical monism; metaphysical pluralism; taxonomic pluralism; essentialism; Ereshefsky